ANALYSIS OF TRENDS IN MEDIA COVERAGE REGARDING ETHNIC, SOCIAL, AND CULTURAL DIVERSITY: EXPERIENCE OF FOUR RUSSIAN REGIONS - Elvira Tagirovna Mayboroda (Вестник Северо-Кавказского федерального университета, 2022)
The item describes the outcomes of a project aiming at studying the regional experience of shaping informational news agenda when covering ethnic-social and ethnic-political, as well as migration issues. The study was held in the second half of 2013 in four Russian regions, the aim of that being to find out how the regional media cover ethnic-cultural, ethnic-religious, social issues, and migration processes, as well as the representation of migrants and other vulnerable social or ethnic groups.